FAKTOR-FAKTOR YANG MEMENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR - Suwita, Elcent Winata Hadi; Dewi, Sofia Prima (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The purpose of this study was to obtain empirical evidence regarding the effect of profitability, firm size, asset structure, sales growth, and firm age on capital structure. The method used to select the sample is purposive sampling and obtained as many as 39 samples of manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. The selected sample will be processed using the Eviews 12 Student Version program and Microsoft Excel. The results shown in this study are that profitability and asset structure have a negative effect on capital structure, firm size and sales growth do not have a positive effect on capital structure, while company age does not negatively affect capital. The implication of this research is that companies need to pay attention to profitability and asset structure to maximize the company's capital structure.